Pengaruh Gaya Kepemimpinan dan Disiplin terhadap Kinerja Pegawai Desa Srimukti Tambun Utara - Rubiah Fitriyanti; Ina Sawitri; Mega Indah Edityawati; Krisna Sudjana; Rizal Bakti; Ayu Lestari (Departement of Mathematics Education, 2023)
In essence, humans are social creatures who live in groups, so it cannot be denied that in everyday life humans cannot be separated from various kinds of problems, one of which is in organization. Performance is something that must be improved by every agency in implementing programs that are directed to always be efficient to achieve agency goals. Organizational progress is achieved when employee performance is high, which is influenced by the leadership style of the leader and discipline. The purpose of this study was to determine and analyze the influence of Leadership Style and Discipline on the Performance of Desa Srimukti Employees. The type of research used is associative research with quantitative research methods in the form of data collection using questionnaires. The number of samples used as many as 30 respondents using multiple linear regression analysis techniques.The results of the regression test showed that 76,8% of the performance factors could be explained by leadership style and discipline, while the remaining 23,2% was explained by other factors not examined in this study. While the results of the F test show that simultaneously the variables of leadership style and discipline simultaneously have a positive and significant effect on performance with the results of the analysis that the value of Fcount (49.018) > Ftable (3.354). The results of the t test show that the discipline variable shows the results of the t-count analysis (-0,071) where the t table (2.051) then partially the variables dicipline have no significant effect on employee performance Desa Srimukti. The leadership style variable has a positive and significant effect on the performance of employees Desa Srimukti with the value of the t-count analysis (9.816). The dominant variable affecting performance is the leadersip style.